PENGARUH LOKASI, HARGA DAN PROMOSI TERHADAP LOYALITAS KONSUMEN PADA USAHA AYAM GEPREK DV DI SITUBONDO MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Kusuma, Diva Dwi; Karnadi, Karnadi; Fandiyanto, Randika (Fakultas Ekonomi dan Bisnis, 2024)
Marketing is an interconnected activity between companies and consumers as a system for generating profits, therefore having the right marketing strategy can improve it, especially as a means of developing the Ayam Geprek DV restaurant business in Situbondo Regency. The aim of this research is to analyze and test the influence of Location, Price and Promotion on consumer loyalty through consumer satisfaction as an intervening variable. The target population in this study was DV Geprek Chicken consumers, numbering 97 respondents. This sampling technique is simple random sampling. Data analysis and hypothesis testing in research uses Structural Equation Models - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that location has a significant positive effect on consumer satisfaction. Price has a significant positive effect on consumer satisfaction. Promotion has a significant positive effect on consumer satisfaction. Location has a positive but not significant effect on consumer loyalty. Price has a positive but not significant effect on consumer loyalty. Promotion has a significant positive effect on consumer loyalty. Consumer satisfaction has a significant positive effect on consumer loyalty. Then the results of the indirect effect hypothesis test show that the location variable on consumer loyalty through consumer satisfaction has a significant positive effect. Price on consumer loyalty through consumer satisfaction has a significant positive effect. Promotion of consumer loyalty through consumer satisfaction has a significant positive effect